Haplotype Analysis of Chloroplast Genomes for Jujube Breeding - Hu, Guanglong; Wu, Yang; Guo, Chaojun; Lu, Dongye; Dong, Ningguang; Chen, Bo; Qiao, Yanjie; Zhang, Yuping; Pan, Qinghua (Frontiers in Plant Science, 2022)
Jujube (family Rhamnaceae) is an important economic fruit tree in China. In this study, we reported 26 chloroplast (cp) sequences of jujube using Illumina paired-end sequencing. The sequence length of cp genome was 161, 367–161, 849 bp, which was composed of a large single-copy region (89053–89437bp ) and a small single-copy region (19356–19362 bp ) separated by a pair of reverse repeat regions ( 26478–26533 bp ). Each cp genome encodes the same 130 genes, including 112 unique genes, being quite conserved in genome structure and gene sequence. A total of 118 SNPs and 130 InDels were detected in 65 jujube accessions. Phylogenetic and haplotype network construction methods were used to analyze the origin and evolution of jujube and its sour-tasting relatives. We detected 32 effective haplotypes, consisting of 21 unique jujube haplotypes and nine unique sour–jujube haplotypes. Compared with sour–jujube, jujube showed greater haplotype diversity at the chloroplast DNA level. To cultivate crisp and sweet fruit varieties featuring strong resistance, by combining the characteristics of sour-jujube and cultivated jujube, three hybrid combinations were suggested for reciprocal crosses: ‘Dongzao’ × ‘Jingzao39’, ‘Dongzao’ × ‘Jingzao60’, ‘Dongzao’ × ‘Jingzao28’. This study provides the basis for jujube species’ identification and breeding, and lays the foundation for future research.